The relationship between consumption of pornography and sexual pleasure: results of a mixed-method systematic review. Issue 3 (3rd July 2021) - McKee, Alan; Litsou, Katerina; Byron, Paul; Ingham, Roger
ABSTRACT: A systematic review of literature on the relationship between consumption of pornography and sexual pleasure found two approaches. One examines masturbatory pleasure produced by engagement with pornography and finds that both men and women take pleasure from pornography consumption (although for women, in particular, this can create conflicting reactions). A second, more dominant, approach investigates whether pornography consumption is associated with subsequent sexual pleasure with a partner. It is notable that even in a sample of articles curated to understand pleasure, there is more research into satisfaction than pleasure and, in particular, relationship satisfaction.